Pendekatan Agile Leadership dalam Menanggulangi Masalah Anak Terlantar di Kawasan Perkotaan: Studi di Kota Pekanbaru - Suriani, Lilis; Karya, Detri; Paman, Ujang (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2025)
The problem of homelessness and begging in Pekanbaru requires an adaptive approach to address the ever-changing social dynamics. This study explores the application of Agile Leadership as a strategy to increase the effectiveness of social interventions in addressing homelessness and begging. The method used is the Systematic Literature Review (SLR) method. Furthermore, data obtained from the literature selection results were then analyzed using a descriptive approach to explore the application of Agile Leadership in the context of addressing neglected children in urban areas. The research findings indicate that Agile Leadership allows for faster policy adjustments based on field feedback and social conditions. Collaboration between the government and local communities has been shown to increase program effectiveness, while a data-driven approach supports more accurate decision-making. The implications of this study indicate that with adaptive and collaborative strategies, the city government can create more effective and sustainable interventions in addressing the problem of neglected children. This research contributes to the understanding of the application of adaptive leadership in urban governance and can serve as a reference for other cities facing similar challenges.